What do new performance metrics, VeDBA and Dynamic yaw, tell us about energy-intensive activities in whale sharks? - ABIGAIL BUXTON (2023)
During oscillatory dives, whale sharks (Rhincodon typus) expend varying levels of energy in active ascent and passive descent. They are expected to minimise movement costs by travelling at optimum speed unless having reason to move faster, for example during feeding or evasion of danger. A proxy for power, dynamic body acceleration (DBA) has previously been used to identify whale shark movement patterns but has yet been used to identify occasions where power is elevated above minimum requirements. 59 hours of biologging data from 13 juvenile whale sharks (Ningaloo Reef, Western Australia) including depth, body pitch angle, magnetometry and DBA, was analysed to investigate minimum power requirements for dives and identify events of elevated power. Dynamic yaw (the rate of change of heading), a new proxy for power, was introduced to determine its effectiveness compared to the already-established DBA. The relationship between pitch angle and these two proxies was investigated to determine which had the stronger relationship. Dynamic yaw produced a poor relationship with pitch angle compared to DBA, and thus DBA was selected as the focus proxy for the remainder of the study. DBA was utilised to produce a minimum power trend versus body pitch angle using a convex hull analysis which allowed for the identification of proxy for power utilisation above the minimum (PAM). 16 instances of PAM were identified in 59 hours of data, which could all be considered instances where energy minimisation is not prioritised, such as feeding or avoidance. The PAM method was capable of identifying instances where energy minimisation is not prioritised, and therefore has future implications in investigations of location-specific behaviours in relation to feeding and anthropogenic disturbance.